The Islamic Reformist Movement in the Malay-Indonesia World in the First Four Decades of the 20th Century: Insights Gained from a Comparative Look at Egypt - Giora Eliraz (Studia Islamika, 2002)
The transmission of Islamic reformist ideas from the Middle East, in particular from Egypt, to the Malay-Indonesian world stimulates interest in observing and examining this formative chapter in the history of the Islamic reformist movement in the Malay-Indonesian world by taking a comparative look at Egypt. Similarly, an observer of both the center of Islamic world and its "periphery" is surely tempted to try to link them. Hence, this article aims to search for the insights that may derive from such a comparative view. Of course, a comparative view of this type also has basically vulnerable points and biases which will be mentioned in this particular context in the course of the discussion. Not with-standing, it appears that taking Egypt as a comparative case study vis-a-vis the Malay-Indonesian world in this regard may enrich knowledge about this fascinating chapter in the modern history of the reformist movement in the Malay-Indonesian world. Perhaps it may even provide insights regarding the movement that go beyond the confines of the said period.DOI: 10.15408/sdi.v9i2.666